Erasmus Intensive Programmes focusing on care of the elderly: An innovative Nursing Educational Tool? - Dimitrios Theofanidis; Antigoni Fountouki (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Introduction: The Erasmus Intensive Programme (IP) is a short term programme of study lasting from 10 continuous days to a maximum of six weeks of subject related work by bringing together students and staff from higher education institutions of at least three EU countries. Aim: The purpose of this paper is to describe the content of a sequence of three IPs on older people's care and describe their relevance in contemporary nursing education. Method: This discussion paper uses refl ective analysis via presentation of the key features of the three IPs i.e.: Aims, Objectives, Target groups, Main activities, Learning Outcomes and Outputs followed by a short reflective commentary on each IP by the lead participant. Results: Students and staff involved have demonstrated enthusiasm for the three EIPs ability to foster new curricula approaches and innovative educational skills such as open exchanges of views, cross cultural exchange of ideas, in a truly multinational classroom environment. Conclusions: IPs benefi ted students and staff involved by broadening their horizons concerning health care for the elderly. Also, students learned from cross-cultural stimulation and non-conventional ways of problem solving and subsequently gained new perspectives on their chosen professions. Similarly, tutors benefi ted from unique insights into different ways of teaching and motivation techniques.